Surviving Death by Leslie Kean - Goertzel, Ben (Journal of Scientific Exploration, 2017)
Leslie Kean’s Surviving Death is a wonderfully readable, carefully constructed summary of the evidence for the existence of what is colloquially called an “afterlife.” That is, she considers evidence for the hypothesis that individual human minds and personalities possess an existence going beyond their attachment to any particular body – so that, for instance, an individual with a certain name and certain traits may sometimes continue to perceive and act, even when the body typically associated with that individual is dead and gone. Most of the book comprises moderately detailed descriptions of specific cases, involving specific people, which indicate the existence of some sort of “afterlife” for individual human minds, or potentially give some information regarding the nature of this afterlife. Kean considers a gamut of phenomena such as past-life memories, near-death experiences, mediumistic trances, poltergeists, and so forth. However, she also makes a significant effort to draw general conclusions, lessons and hypotheses from the totality of these cases, while maintaining respect for the confusing and in many ways still mysterious nature of the phenomena under discussion. Each of the topics considered in the book has been reviewed and analyzed in more depth elsewhere. What Kean does, however, is provide a clear, evocative and rational survey of the many types of evidence that are directly relevant to the possibility and nature of an afterlife for individual human minds.